Pellet counts and Habitat survey from Grimsö, Centroid of Research Area - Grimsö Wildlife Research Station (Swedish University of Agricultural Sciences, 2025)
Inventory of pellet and dropping counts including habitat survey based on 32 transects equally spread throughout the Grimsö Wildlife Research Area (GWRA) contain in total 600 plots (area 100 m2). These plots are surveyed in Spring for moose pellet piles and habitat data, and in Fall for only pellets. Along each of those plots, there are 4 smaller plots (10 m2, total n=2400) used for surveying pellets and droppings from five small game species. After each visit (Spring and Fall), the plots are cleared from pellets and droppings.
Grimsö Wildlife Research Station (2025). Pellet counts and Habitat survey from Grimsö, Centroid of Research Area, 1997–2025 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/V-Gf_0cFk9wyJ2QXFCuBqCVR
Keywords: Grimsö Wildlife Research Station; Deer/moose; Population Dynamics; Year; Year; Count; Count; Proportion; Proportion; Mean top-shoot length; Mean top-shoot length; Sample size; Sample size; Mean browsing pressure; Mean browsing pressure; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap